Pemberdayaan Anak Terlantar dalam Program Rehabilitasi Sosial: Analisis Pendekatan 5P di Rumah Pelayanan Sosial “Mandiri” Kota Semarang - Najwa Aulia Larasati; Lusia Astrika (Journal of Politic and Government Studies, 2026)
The state holds a constitutional mandate to care for neglected children, partly through social rehabilitation programs that should move beyond meeting basic needs to empowering children to determine their own futures. This study analyzes how the empowerment of neglected children is realized within the social rehabilitation program at the Rumah Pelayanan Sosial “Mandiri” in Semarang City, while identifying its driving and inhibiting factors. Employing a descriptive qualitative approach, the study uses Edi Suharto’s 5P empowerment framework (Enabling, Empowering, Protecting, Supporting, and Fostering) and viewed from a child rights perspective as its analytical lens. Data were gathered through in-depth interviews with the Head of Social Rehabilitation at the Central Java Provincial Social Service, the institution’s head and functional social workers, and beneficiaries, supplemented by observation and documentation, then validated through source triangulation. The findings reveal that empowerment has occurred but remains suboptimal, constrained by a persistent gap between normative design and field reality. While the institution successfully fosters a safe environment and expands access to formal education, the transformative essence of empowerment is not fully achieved: children tend to be positioned as objects of service rather than as subjects who understand and shape their own choices. The Fostering dimension is the weakest, as post-termination guidance relies solely on personal initiative without institutional support. The most fundamental obstacle is the shortage of social workers, with caseload ratios of 1:12 to 1:13, alongside budget constraints, whereas visionary leadership and personal dedication serve as primary enablers. The study recommends increasing social worker numbers, adopting needs-based budgeting, and institutionalizing aftercare programs.